Olimpíada de língua portuguesa: expectativas, interpretações e práticas na voz de professores de ensino médio do distrito 6 da zona norte de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This work had as general objective to analyze the action of the training workshops of the Portuguese Language Olympiad in the voice of Portuguese language teachers and, as specific, to verify if the workshops affect the teaching concept in relation to language teaching and how to investigate if workshops interfere in the practice of the Portuguese language teacher and how and learn the role of PLO training workshops for the LP teacher. The theoretical framework addressed historical issues related to the teaching of the Mother Language in basic education based in Brazil (1998; 2002), Freire (2004), Mendonça (2014) and Soares (2004), the Portuguese Language in High School based on Antunes (2009) ), Brazil (2002; 2006; 2008; 2017 [1996]), Mendonça and Bunzen (2006) and Faraco (2008), the production of texts written in Portuguese language classes supported by Bunzen (2006), Geraldi (1997) and Marquesi (2014). As for the Portuguese-speaking Olympics, it was based on Dolz (2011), Dolz, Noverraz and Schneuwly (2004); Marcuschi (2010); Rangel and Garcia (2012) and Setúbal (2008). Anchored in these theoretical contributions, the research was based on the qualitative paradigm (CRESWEEL, 2007; MICHALISZYN; TOMASINI, 2012; SEVERINO, 2007; STRAUSS; CORBIN, 2008), in the light of an interpretive study (BORTONI-RICARDO, 2008). Interviews and two questionnaires were used for data generation, one in profile and the other investigative (LAKATOS; MARCONI, 2002; MONTEIRO, 2009). The context of the research was three high schools in District 6 in the north of Manaus. The results indicated that teachers see continuing education as a “technical course”, about how to teach, in other words, a contribution that provides content to be transmitted in the future by them in class. It was also noticed the constitution of an absolutely antagonistic conception between the traditional view and the one currently in vogue about the teaching of the mother tongue, emerging in the speech of one of the teachers a certain pride in saying “I am traditional”, as if that give a legitimacy or a different quality in teaching.
Keywords: Análise do discurso; Língua portuguesa (Ensino médio); Olimpíada de língua portuguesa; Língua portuguesa - Estudo e Ensino; Prática profissional; LINGUÍSTICA, LETRAS E ARTES; Olimpíada de língua portuguesa; Ensino; Formação continuada; Oficinas de preparação